Kajian Proses Fermentasi Sludge Kotoran Sapi - I Putu Gde Suhartana; Yohanes Setiyo; I Wayan Widia (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
This research aimed to determine the effect of air circulation treatment toward cow manure sludge fermentation process and to determine the quality of sludge that was produced accordance to Indonesia National Standard (SNI) of Compost No. 19-7030-2004. The air circulation treatment was done by using aerator. There were three combination treatments of air circulation: the aerator and drum with coat, aerator and drum without coat, and without aerator and drum without coat was applied as a control. The results of this study indicate that each treatment in the fermentation process had a different temperature fluctuations between 21.56 to 24.41 °C. Temperature is a requirement for mesophilic microbial growth. The acidity condition of the sludge material at the beginning until the end of fermentation was the whole treatment has fulfilled the optimal conditions of fermentation process, with range of pH was from 6.92 to 7.65. The influence of air circulation inside the drum without the coat of rice husk can accelerate the breakdown of proteins into C-organic and N-total, that was C-organic= 24.22%, and N-total = 1.80%. The compost that produced by the fermentation process had the characteristic ratio C / N = 13.46 and had a blackish brown colour rendition. Characteristics of compost according to the quality of compost SNI No. 19-7030-2004, that is pH = 6.80 to 7.49, C-organic = 9.80 to 32%, N-total = 0.40%, the ratio of C / N = 10-20.